Benefits of Sargassum sp. Extract for Feed Supplementation on the Growth and pH Shock Resistance of Zebrafish (Danio rerio) - Yulianto Puguh Arahmad; Reza Rahmadika; Ervia Yudiati; Ali Ridlo; Nuril Azhar (Jurnal Kelautan Tropis, 2026)
Sargassum sp. is an abundant marine biological resource in Indonesia rich in bioactive compounds, yet its utilization as a feed supplement in fish culture remains limited. Feed represents the highest cost component in aquaculture, necessitating economical natural additives to improve fish performance and their resistance to environmental stressors such as pH fluctuations. This research aimed to evaluate the effect of Sargassum sp. water extract, obtained using acidic (pH 3) and alkaline (pH 12) methods, on the survival rate, growth, and resistance of zebrafish (Danio rerio) to extremely low pH shock. The study employed a Completely Randomized Design (CRD) with nine treatments (control, four alkaline extract doses, and four acidic doses) over a 30-day rearing period. Doses were determined based on BSLT toxicity tests, which indicated that both extracts were non-toxic (LC50 > 1000 ppm). The parameters observed included survival rate, absolute weight gain, and mortality during a pH 3 shock test. The results showed that supplementation had no significant effect on survival rate (P>0.05). However, all extract treatments (acidic and alkaline) significantly increased absolute weight gain (P<0.05) compared to the control, with the highest average weight found at the lowest alkaline Sargassum sp. extract 1.375 ppm. Fish supplemented with the extract showed significantly lower mortality in the low pH shock test (P<0.05), with the best resistance value observed at the lowest acidic treatment (1,875 ppm). These findings indicate that Sargassum sp. extract has the potential as an effective natural feed supplement to promote growth and enhance the physiological resistance of fish to environmental stress, even at low concentrations.